#1

What are the steps to a proof problem that asks you to prove that each angle in an equiangular triangle is 60 degrees?

#2

Well the sum of the angles of a triangle are 180 degrees. An equiangular triangle is a triangle with all equal angles. 180/3=60

There ya go. Maybe you can word that better though.

There ya go. Maybe you can word that better though.

#3

what's the conjecture/postulate that says triangles are 180 degrees in sum?

#4

*Shrug* Look it up? I have in my head but I forget what it's called.

#5

I think i got it...

Given tri. ABC, prove m<A = 60

m<A + m<B + m<C = 180 by triangle sum conjecture

m<A = 60 by 180/3???

m<A = m<B = m<C = 60 by substitution

Given tri. ABC, prove m<A = 60

m<A + m<B + m<C = 180 by triangle sum conjecture

m<A = 60 by 180/3???

m<A = m<B = m<C = 60 by substitution

#6

Mention the triangle is equiangular.

#7

I think I'd flip steps 2 and 3 around and say that m<A = m<B = m<C by the definition of an equilateral triangle, and therefore m<A = 60.

#8

is equiangular the same as equilateral?

*Last edited by lp_std at Nov 7, 2007,*

#9

what's the conjecture/postulate that says triangles are 180 degrees in sum?

definition of a triangle

#10

i equiangular the same as equilateral?

Equiangular means all the angles are the same. Equilateral means all the sides are the same. In a triangle, one follows from the other, so yes.

#11

Lol thanks guys, i think i got it although

im not too sure on the 180/3 step...

can it be more formal?

im not too sure on the 180/3 step...

can it be more formal?

#12

wow. i dont understand any of this.

#13

lol I'm sorry but I just find that funny with your user name.

#14

Alright...

Given: tri. ABC is equiangular.

Prove: m<A=60

m<A = m<B = m<C because the triangle is equiangular

The sum of the angles of a triangle are 180 degrees, by Definition of a Triangle.

m<B = 60 degrees, 180/3 = 60

m<A = 60 degrees by transitive property.

That could work.

Given: tri. ABC is equiangular.

Prove: m<A=60

m<A = m<B = m<C because the triangle is equiangular

The sum of the angles of a triangle are 180 degrees, by Definition of a Triangle.

m<B = 60 degrees, 180/3 = 60

m<A = 60 degrees by transitive property.

That could work.

#15

Can we hurry this up? I'm exhausted! Hahaha.

#16

its easy.

proofs are very straight forward, and a lot of people are scared to write stuff because of that.

just say:

triangle is equiangular - (given)

<a + <b + <c = 180 (angles of a triangle = 180 degrees)

180/3 = 60 degrees

therefore <a = 60 deg., <b = 60 deg., <c = 60 deg.

thats a good enough proof of a question like that

proofs are very straight forward, and a lot of people are scared to write stuff because of that.

just say:

triangle is equiangular - (given)

<a + <b + <c = 180 (angles of a triangle = 180 degrees)

180/3 = 60 degrees

therefore <a = 60 deg., <b = 60 deg., <c = 60 deg.

thats a good enough proof of a question like that

*Last edited by instagata0 at Nov 7, 2007,*